2014
DOI: 10.1038/ajg.2013.385
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Magnetic Resonance Imaging in Ileocolonic Crohn's Disease: Validation of Quantitative Index of Activity

Abstract: DW-MREC is a reliable tool to assess inflammation in colonic (ADC) and ileal (Clermont score) CD and its use in daily practice would avoid gadolinium injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
185
6
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(213 citation statements)
references
References 19 publications
13
185
6
4
Order By: Relevance
“…It is also important to underline that in line with the cutoff used in our study to predict the presence of post-operative recurrence of high degree, other authors [34,12] have found similar cut-off, respectively, 1.9 × 10ˉ ³mm²/s and 2.0 x 10ˉ ³mm²/s, capable of discriminating between active and non-active CD in the small intestine, with a sensitivity ranging from 84% and 86% and a specificity between 82% and 91%, while in Buisson's study [35] an ADC<1.88 x 10-3 mm2/s was capable to distinguish superficial endoscopic ulcerations with a Se=64% and a Spe=75% and an ADC<1.42 x 10-3 mm2/s recognised endoscopic deep ulcers with Se=91% and Spe=83%.…”
Section: Post-surgical Recurrence's Evaluationsupporting
confidence: 71%
See 1 more Smart Citation
“…It is also important to underline that in line with the cutoff used in our study to predict the presence of post-operative recurrence of high degree, other authors [34,12] have found similar cut-off, respectively, 1.9 × 10ˉ ³mm²/s and 2.0 x 10ˉ ³mm²/s, capable of discriminating between active and non-active CD in the small intestine, with a sensitivity ranging from 84% and 86% and a specificity between 82% and 91%, while in Buisson's study [35] an ADC<1.88 x 10-3 mm2/s was capable to distinguish superficial endoscopic ulcerations with a Se=64% and a Spe=75% and an ADC<1.42 x 10-3 mm2/s recognised endoscopic deep ulcers with Se=91% and Spe=83%.…”
Section: Post-surgical Recurrence's Evaluationsupporting
confidence: 71%
“…Buisson & Hordonneau [33,34] have found a strong correlation between the two indices in patients with colonic involvement and, although to a lesser degree, of the distal ileum; furthermore has been found good correlation with Clermont score but these quantitative measures are still in process of validation, being understood that these study are limited because didn't use endoscopic findings as reference.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of MRE for quantitative evaluation of SB inflammation in CD is established [Rimola et al 2009[Rimola et al , 2011Ordas et al 2014]; a novel MRE-based index [Magnetic Resonance Index of Activity (MaRIA) score] demonstrated significant correlation with the Crohn's Disease Endoscopic Index of Activity (CDEIS) [Rimola et al 2011;Ordas et al 2014]. Diffusion-weighted (DW)-MRE yields comparable performance and does not require intravenous contrast material [Hordonneau et al 2014]. The DW-MRE-based Clermont index, which incorporates the apparent diffusion coefficient (ADC), was recently validated in distal SB CD and was strongly correlated with MaRIA and the Simple Endoscopic Score for CD (SES-CD) [Caruso et al 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Taigi gydymo efektyvumui įvertinti reikalingas išsamus gleivinės ir žarnos sienelės stebėjimas. Panašu, kad šiuo metu MRE -geriausia alternatyva endoskopiniam tyrimui [8].…”
Section: Rezultatų Aptarimasunclassified